Implementation Of Tbl Model (Team-Based Learning) Assisted Video Media To Improve Learning Performance Of Class Xi Ips 3 Subject History At Man 1 Jember In The 2016/2017 Academic Year - Yuanita, Erva; Naim, Mohamad; Soepeno, Bambang (History Education, University of Jember, 2017)
Based on the percentage of classical completeness of learning performance of learners are on the criteria less reflected from the low ability of learners related to material absorption, analytical skills, problem-solving, learning products and learning attitudes. With regard to such matters, a problem solving is required through classroom action research by applying of TBL (Team-Based Learning) model assisted by media video. The purpose of this study is to assess the improvement of learning performance in class XI IPS 3 MAN 1 Jember after the application of TBL model assisted by video media. This research is a classroom action research conducted for three cycles with Kemmis and Mc Tagart model. The sample of the research is the students of class XI IPS 3 MAN 1 Jember a number of 33 students. Data were analyzed quantitatively. Learning performance was measured using five indicators including affective, cognitive and psychomotor spheres while research data was obtained through observation, interview, documentation and test. The result of the research shows that the improvement of learning performance includes: (1) process performance with the percentage of classical completeness equal to 74,66%; (2) the performance of the results obtained a percentage of classical completeness of 77.77% and; (3) the affective domain obtained a percentage of classical completion of 75.75%. Based on the results of research, it can be concluded that the application of TBL model assisted by video media able to improve learning performance include affective, cognitive and psychomotor span. The implication of the writing of this scientific paper is to contribute to the field of education as one of the inputs in overcoming the problem of learning performance in history subjects as well as a contribution to further research related to the model of TBL, video media and learning performance. Keyword: model TBL (team based learning), video media, learning performance